Improving accessibility and discovery of ESA planetary data through the new planetary science archive. (January 2018) - Macfarlane, A.J.; Docasal, R.; Rios, C.; Barbarisi, I.; Saiz, J.; Vallejo, F.; Besse, S.; Arviset, C.; Barthelemy, M.; De Marchi, G.; Fraga, D.; Grotheer, E.; et al.
Abstract: The Planetary Science Archive (PSA) is the European Space Agency's (ESA) repository of science data from all planetary science and exploration missions. The PSA provides access to scientific data sets through various interfaces athttp://psa.esa.int . All data sets are scientifically peer-reviewed by independent scientists, and are compliant with the Planetary Data System (PDS) standards. Mostly driven by the evolution of the PDS standards which all new ESA planetary missions shall follow and the need to update the interfaces to the archive, the PSA has undergone an important re-engineering. In order to maximise the scientific exploitation of ESA's planetary data holdings, significant improvements have been made by utilising the latest technologies and implementing widely recognised open standards. To facilitate users in handling and visualising the many products stored in the archive which have spatial data associated, the new PSA supports Geographical Information Systems (GIS) by implementing the standards approved by the Open Geospatial Consortium (OGC). The modernised PSA also attempts to increase interoperability with the international community by implementing recognised planetary science specific protocols such as the PDAP (Planetary Data Access Protocol) and EPN-TAP (EuroPlanet-Table Access Protocol). In this paper we describe some of the methods by which the archive may be accessed and present the challenges that are being faced in consolidating data sets of the older PDS3 version of the standards with the new PDS4 deliveries into a single data model mapping to ensure transparent access to the data for users and services whilst maintaining a high performance.